Bearing Behavior of H-Shaped Honeycombed Steel Web Composite Columns with Rectangular Concrete-Filled Steel Tube Flanges under Eccentrical Compression Load - Jing Ji; Chenyu Yu; Liangqin Jiang; Jiedong Zhan; Hongguo Ren; Sixue Hao; Shaojie Fan; Li Jiang; Yubo Lin; Lingjie He (Advances in Civil Engineering)
In order to investigate the bearing capacity of H-shaped honeycombed steel web composite columns with rectangular concrete-filled steel tube flanges (STHCCs) subjected to eccentrical compression load, 33 full-scale STHCCs were designed with the eccentricity(e), the slenderness ratio (λ), the cubic compressive strength of concrete(fcuk), the thickness of the steel tube flange (t1), the thickness of honeycombed steel web (t2), diameter-depth ratio (d/hw), space-depth (s/hw), and the yield strength of the steel tube (fy) as the main parameters. Considering the nonlinear constitutive model of concrete and simplified constitutive model of steel, the finite element (FE) model of STHCCs was established by ABAQUS software. By comparison with the existing test results, the rationality of the constitutive model of materials and FE modeling was verified. The numerical simulation of 33 full-scale STHCCs was conducted, and the influence of different parameters on the ultimate eccentrical compression bearing capacity was discussed. The results show that the cross-sectional stress distribution basically conforms to the plane-section assumption. With the increase in e, λ, and d/hw, the ultimate eccentrical compression bearing capacity of the full-scale STHCCs decreases, whereas it gradually increases with the increase in fcuk, t1, t2, s/hw, and fy. By introducing bias-stress stability coefficient (φ), the calculation formula of full-scale STHCCs under eccentrical compression is proposed by statistical regression, which can lay a foundation for the popularization and application of these types of composite columns in practical engineering.